Body Composition and Power Performance Improved After Weight Reduction in Male Athletes Without Hampering Hormonal Balance. Issue 1 (January 2015) - Huovinen, Heikki T.; Hulmi, Juha J.; Isolehto, Juha; Kyröläinen, Heikki; Puurtinen, Risto; Karila, Tuomo; Mackala, Krzysztof; Mero, Antti A.
Abstract : Abstract: Huovinen, HT, Hulmi, JJ, Isolehto, J, Kyröläinen, H, Puurtinen, R, Karila, T, Mackala, K, and Mero, AA. Body composition and power performance improved after weight reduction in male athletes without hampering hormonal balance. J Strength Cond Res 29(1): 29–36, 2015—The aim of this study was to investigate the effects of a 4-week weight reduction period with high protein and reduced carbohydrate intake on body composition, explosive power, speed, serum hormones, and acid-base balance in male track and field jumpers and sprinters. Eight participants were assigned to a high weight reduction group (HWR; energy restriction 750 kcal·d −1 ) and 7 to a low weight reduction group (LWR; energy restriction 300 kcal·d −1 ). Energy and carbohydrate intake decreased significantly ( p ⩽ 0.05) only in HWR by 740 ± 330 kcal·d −1 and 130 ± 29 g·d −1, respectively. Furthermore, total body mass and fat mass decreased ( p ⩽ 0.05) only in HWR by 2.2 ± 1.0 kg and 1.7 ± 1.6 kg, respectively. Fat-free mass (FFM), serum testosterone, cortisol, and sex hormone–binding globulin did not change significantly. Ca 2+ ion and pH decreased ( p ⩽ 0.05) only in HWR (3.1 ± 2.8% and 0.8 ± 0.8%, respectively), whereas declined ( p ⩽ 0.05) in both groups by 19.3 ± 6.2% in HWR and by 13.1 ± 8.5% in LWR. The countermovement jump and 20-m sprint time improved consistently ( p ⩽ 0.05) only in HWR, by 2.6 ± 2.5 cm and 0.04 ± 0.04 seconds, respectively. Finally, athletes with a fat percentage of 10% or more at the baseline were able to preserve FFM. In conclusion, altered acid-base balance but improved weight-bearing power performance was observed without negative consequences on serum hormones and FFM after a 4-week weight reduction of 0.5 kg·wk −1 achieved by reduced carbohydrate but maintained high protein intake.